The librarian stereotype: How librarians are damaging their image and profession. Issue 1 (2nd January 2016) - Jennings, Eric
ABSTRACT: Every profession has a stereotype, and librarians are no stranger to this phenomenon. This article discusses the stereotype, how librarians have responded to its use in the public sphere, and reasons why the author sees the profession's reaction as problematic.